THE ANALYSIS OF THE ECO-TOURISTIC ACCOMMODATION LABELLING IN HUNGARY AND CROATIA - Horváth, Andrea (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
The types of tourism which are destined for reducing the negative effects of mass tourism, like ecotourism, mild tourism and green tourism appeared at the end of the 20th century. The approach has changed, visiting natural and cultural values has become one of the main motivations of the tourists who are responsible for their environment. This change of approach has become necessary for the touristic service providers, who are the important pillars of the touristic superstructure. The eco-touristic labelling system was introduced some years ago in South Transdanubia, Hungary. The highest obtainable rank is the three “hellebores”. One can label the ecotouristic service providers in three categories, for instance the accommodation, the catering and the services/events. We had done some labels therefore we were able to analyse whether the criteria system was living or not, in which section the touristic service providers performed the best and what were their most common difficulties. During the research it turned out that the criteria system must be changed at some points. Because of the differences between the capacity of accommodation it is essential to reconsider or change some terms, regarding their necessity.